Sensors for Mechatronics - Regtien, Paul P. L. (Elsevier Science, 2012)
Mechatronics is a multidisciplinary field combining Mechanical, Electronic, Computer, and other Engineering fields to develop intelligent processes and products. Based on thirty years of extensive work in industry and teaching, this book provides an overview of the sensors and sensor systems required and applied in mechatronics with an emphasis on understanding the physical principles and possible configurations of sensors rather than simply a discussion of particular types of sensors. Well illustrated with examples of commercially available sensors and of recent and future developments, this book offers help in achieving the best solution to various kinds of sensor problems encountered in mechatronics. In a clear and detailed manner, the author reviews the major types of transducers, presents a characterization of the state-of-the-art in sensing technology and offers a view on current sensor research. This book will be a vital resource for practicing engineers and students in the field.
Keywords: Mechatronics.; Mechatronics -- Congresses.; Process control -- Automation -- Congresses.; Detectors.; Engineering.; elektronické knihy; electronic books